THU0076 Disease-modifying treatment regimens have been insufficient to reduce the incidence of systemic aa amyloidosis associated with rheumatoid arthritis in contrast to a significant reduction in those with juvenile idiopathic arthritis. (15th June 2017) - Youngstein, TA-B; Lane, T; Gilbertson, J; Pinney, J; Rezk, T; Manwani, R; Quarta, CC; Wechalekar, A; Mahmood, S; Sachchithanantham, S; Fontana, M; Whelan, C; et al.
Abstract : Background: The UK National Amyloidosis Centre has the largest known cohort of individuals with AA amyloidosis, with 660 cases since 1990. A third present in end stage renal failure (33%), with a median survival of 133 months from diagnosis 1 . Over 27 years the rate of new cases has remained remarkably constant with a median of 24 diagnoses per annum (IQR 18.5–30.5) but responsible for a decreasing proportion of new cases of systemic amyloidosis from 35% in the first 5 years to 6% in the last 5 years of the cohort. Objectives: We sought to determine to what extent advances in treatment of the inflammatory arthritides have influenced the aetiology of AA Amyloidosis over time. Methods: Retrospective analysis of the UK National Amyloidosis Centre AA Amyloidosis database containing baseline demographic and clinical data. Data was analysed using a Chi-squared test (GraphPad Prism 7.0). Results: Between 1990–2000 there were 188 new cases of AA Amyloidosis of which 51 (27.1%) had an underlying diagnosis of rheumatoid arthritis (RA), median age at diagnosis of amyloid was 60 years. 37 (19.7%) had a diagnosis of Juvenile Idiopathic Arthritis (JIA), median age 29 years. Between 2007 and 2017 there were 270 new diagnoses of AA Amyloidosis, of whom 57 had RA (21.1%), median age 66 years, and 5 (1.9%) had JIA, median age 37 years. Since the widespread use of combination disease-modifying and biologic therapy there has been a significant reduction in the incidence of JIA-associated AA Amyloidosis (p<0.0001). In contrast, the incidence of RA-associated AA Amyloidosis is unchanged (p<0.1357). Conclusions: Advances in the treatment of JIA have significantly reduced the incidence of AA Amyloidosis in this cohort. In contrast, despite largely the same medication and similar treatment targets, RA continues to be responsible for a substantial proportion of new cases of AA Amyloidosis. One possible explanation for this may be that current assessment of disease activity in RA is sufficient to identify those at risk of joint damage or radiological progression of disease but insufficient for identifying peristent subclinical biochemical inflammation. One approach for reducing this risk may be the routine measure of the AA Amyloid precursor protein, serum Amyloid A protein (SAA) in those with RA, as it is well established that levels of SAA of below 10mg/L prevents the accumulation of AA Amyloid in those with inflammatory disease. References: Lachmann, H. J., Goodman HJ, Gilbertson JA, Gallimore JR, Sabin CA, Gillmore JD, Hawkins PN (2007). Natural history and outcome in systemic AA amyloidosis. N Engl J Med 356(23): 2361–2371. Disclosure of Interest: None declared